1998
DOI: 10.1111/j.1151-2916.1998.tb02606.x
|View full text |Cite
|
Sign up to set email alerts
|

R‐Curve Behavior of Silicon Nitride Ceramic Reinforced with Silicon Carbide Platelets

Abstract: Si 3 N 4 ceramics reinforced with SiC platelets were fabricated by hot pressing at 1800°C. The microstructure of the Si 3 N 4 matrix itself was the same with or without the addition of the SiC platelets. However, the mechanical properties of the Si 3 N 4 were changed remarkably by the SiC addition. The fracture toughness and the crack resistance with crack propagation (R-curve behavior) were improved while the fracture strength was decreased slightly by the platelets. Improvement in crack resistance was attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…1(B), were believed to be responsible for the increase in the fracture toughness. 15 On the other hand, when 20% SiC n was added (MC-2), the strength remained about the same while the fracture toughness was reduced remarkably. Previous results also showed that even though the high-temperature strength and the oxidation resistance were improved significantly, the room-temperature strength was not much changed by the addition of SiC nanoparticle.…”
Section: Resultsmentioning
confidence: 98%
“…1(B), were believed to be responsible for the increase in the fracture toughness. 15 On the other hand, when 20% SiC n was added (MC-2), the strength remained about the same while the fracture toughness was reduced remarkably. Previous results also showed that even though the high-temperature strength and the oxidation resistance were improved significantly, the room-temperature strength was not much changed by the addition of SiC nanoparticle.…”
Section: Resultsmentioning
confidence: 98%